Acyclovir (Zovirax) in herpetic disciform keratitis. Issue 2 (February 1983) - Collum, L M; Logan, P; Ravenscroft, T
Abstract : Forty patients with disciform keratitis were randomly assigned to double-blind treatment with 3% acyclovir and 0.01% betamethasone drops or acyclovir and matching placebo. All patients who received the combination healed in a median time of 21 days, while 11 of 19 patients who received acyclovir alone were withdrawn because their condition remained static or worsened (p less than 0.001). The combination therapy produced a faster rate of healing (p = 0.004); other clinical parameters also improved more favourably in the combination treatment group. Three patients had mild transient punctate keratopathy, but no serious adverse effects were seen despite treatment for a median duration of 28 days in the acyclovir group and 38 days in the combined therapy group. A combination of acyclovir and dilute steroid drops is effective in the management of disciform keratitis.